Mass outflow of the X-ray emission line gas in NGC 4151. Issue 3 (14th February 2020) - Kraemer, S B; Turner, T J; Couto, J D; Crenshaw, D M; Schmitt, H R; Revalski, M; Fischer, T C
ABSTRACT: We have analysed Chandra /High Energy Transmission Gratings spectra of the X-ray emission line gas in the Seyfert galaxy NGC 4151. The zeroth-order spectral images show extended H- and He-like O and Ne, up to a distance r ∼ 200 pc from the nucleus. Using the first-order spectra, we measure an average line velocity ∼−230 km s −1, suggesting significant outflow of X-ray gas. We generated cloudy photoionization models to fit the first-order spectra; the fit required three distinct emission line components. To estimate the total mass of ionized gas and the mass outflow rates, we applied the model parameters to fit the zeroth-order emission line profiles of Ne ix and Ne x . We determined the total mass of ≈5.4 × 10 5 M⊙ . Assuming the same kinematic profile as that for the [O iii ] gas, derived from our analysis of Hubble Space Telescope /Space Telescope Imaging Spectrograph spectra, the peak X-ray mass outflow rate was ≈1.8 M⊙ yr −1, at r ∼ 150 pc. The total mass and mass outflow rates are similar to those determined using [O iii ], implying that the X-ray gas is a major outflow component. However, unlike the optical outflows, the X-ray outflow rate does not drop off at r > 100 pc, which suggests that it may have a greater impact on the host galaxy.